Pronuclear Injection‐Based Targeted Transgenesis. (13th February 2018) - Schilit, Samantha L.P.; Ohtsuka, Masato; Quadros, Rolen M.; Gurumurthy, Channabasavaiah B.
Abstract: Microinjection of DNA expression cassettes into fertilized zygotes has been a standard method for generating transgenic animal models. While efficient, the injected DNA integrates randomly into the genome, leading to potential disruption of endogenous genes or regulatory elements, variation in copy number, or integration into heterochromatic regions that inhibit transgene expression. A recently developed method addresses such pitfalls of traditional transgenesis by targeting the transgene to predetermined sites in the genome that can safely harbor exogenous DNA. This method, called Pronuclear Injection‐based Targeted Transgenesis (PITT), employs an enzymatic transfer of exogenous DNA from a donor vector to a previously created landing‐pad site in the mouse genome. DNA transfer is achieved using molecular tools such as the Cre‐ LoxP recombinase and PhiC31‐ attB / P integrase systems. Here, we provide protocols for performing PITT and an overview of the current PITT tools available to the research community. © 2016 by John Wiley & Sons, Inc.